Using structural equation modelling to investigate the mediating effects of TPACK on intention to use technology - Madzamba, Havatidi; Matorevhu, Alois (Univeritas Papua, 2024)
This article aims to understand, through structural equation modelling (SEM), how the knowledge of technological pedagogical and content knowledge (TPACK) mediates the intention to accept and use technology by teachers’ college lecturers. The ultimate aim is to come up with a sem-generated model which teacher training colleges can use to train lecturers in technology use. Structural equation modeling is a sophisticated multivariate statistical process that enables researchers to analyze the direct and indirect effects of variables on one another, construct theoretical concepts, test the reliability of their measurements, hypothesize and test a theory about their relationships, and account for measurement errors. A questionnaire founded on the unified theory of acceptance and use of technology (UTAUT) was employed to gather data from instructors at ten teacher-training colleges. Simple random sampling was used to select 300 valid questionnaires used in the analysis. Statistic package R was used to run SEM and the results confirmed the mediating role of TPACK in the behavior intention to accept and use technology by lecturers.